Spectroscopic and Electrochemical Studies on the Interaction of Epirubicin with Fish Sperm DNA - R. Hajian; E. Ekhlasi; R. Daneshvar (E-Journal of Chemistry)
The interactions between epirubicin (EPR) and double stranded DNA (ds-DNA) have been studied by UV-Vis spectrophotometry, cyclic voltammetry, fluorescence spectroscopy and viscometery. The apparent binding constant of epirubicin with DNA was found to be 3.8 × 105 mol-1 L and was studied at different temperatures. It indicated that the former method could be successfully applied to the determination of epirubicin. Also, the voltammetric behavior of EPR was investigated at glassy carbon electrode using cyclic voltammetry. Thermodynamic parameters including ∆H0, ∆G0 and ∆S0 were determined as -5.7×104, -3.13×104 J mol-1 and -87.96 J mol-1 K-1 respectively. One indication of the strong interaction between DNA and EP was increasing of viscosity. The diffusion coefficients of EP in the absence (D0)f and presence of ds-DNA (D0)b was calculated as 5.04×10-6 and 1.13×10-6 Cm2 s-1 respectively. According to the thermodynamic parameters, the main binding force could be judged. The experimental results revealed that EPR and ds-DNA had strong interactions. The mechanism of quenching belonged to static quenching and the main sort of binding force was intercalation.